Hospital transfer for patients with postpartum hemorrhage in Yokohama, Japan: a single‐center descriptive study. Issue 1 (22nd December 2021) - Shimada, Kosuke; Taniguchi, Hayato; Enomoto, Kimiko; Umeda, Sayo; Abe, Takeru; Takeuchi, Ichiro
Abstract : Aim: To describe the transport time and timing of transfer of patients with postpartum hemorrhage to a tertiary care institution in an urban area. Methods: We included patients with postpartum hemorrhage transferred to our hospital from a perinatal care facility. We defined transfer time as the time between the referring physician's request for transfer and the patient's arrival at our hospital. We examined transfer time and its breakdown, the shock index before and after transfer, and the prognosis. Results: Overall, 79 patients with postpartum hemorrhage were transported to our hospital within a median (interquartile range) of 53 min (47–63 min). In 70 cases (89%), the request for transport was made before the shock index reached 1.5, and two cases had cardiac arrest during transport. Conclusions: Most patients who were transferred to our hospital were transferred according to the criteria recommended by the guideline. However, the occurrence of cardiac arrest during transport indicates the need to shorten the time from transfer requests to emergency calls by strengthening cooperation with regional perinatal care facilities. Abstract : Seventy‐nine patients with postpartum hemorrhage were transported to our hospital within a median (interquartile range) of 53 min (47–63 min). In 70 cases (89%), the request for transport was made before the shock index reached 1.5, and two cases had cardiac arrest during transport.